Predictive value of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and monocyte-to-lymphocyte ratio for three-year survival in patients with early esophageal cancer undergoing endoscopic submucosal dissection - Zheng, Yanfang; Zhang, Hong; Su, Yuchen; Zhang, Jie; Xu, Wei; Pan, Weihao; Li, Zhigang (Frontiers in Oncology, 2026)
BackgroundEndoscopic submucosal dissection (ESD) has been widely applied as an effective treatment for early esophageal cancer. However, long-term prognosis after surgery remains highly variable. This study aimed to evaluate the clinical value of NLR, PLR, and MLR in patients with early esophageal cancer treated with ESD.MethodsA total of 325 patients with early esophageal cancer who underwent ESD were retrospectively included and categorized into survival and death groups based on their three-year postoperative outcomes. Baseline characteristics between groups were compared using univariate analysis. The Cox proportional hazards model was applied to assess the associations of NLR, PLR, MLR, and their interactions with three-year survival. Restricted cubic spline (RCS) regression was performed to explore the potential nonlinear relationships between NLR, PLR, MLR, and survival outcomes. Receiver operating characteristic (ROC) curves were used to evaluate the predictive ability of NLR, PLR, and MLR for three-year survival.ResultsBaseline characteristics were significantly better in the survival group compared with the death group. The Cox proportional hazards model revealed that higher discharge levels of NLR, PLR, and MLR were significantly associated with increased risk of three-year mortality, with notable synergistic effects observed with tumor location, depth of invasion, tumor size, and margin status. RCS analysis demonstrated significant linear or near-linear associations between NLR, PLR, MLR, and mortality risk. ROC curve analysis indicated that NLR, PLR, and MLR exhibited good predictive performance for three-year survival, with PLR showing superior predictive ability.ConclusionNLR, PLR, and MLR are significantly and positively associated with three-year mortality risk in patients with early esophageal cancer undergoing ESD, in either linear or near-linear patterns. These markers also exhibit synergistic interactions with tumor-related clinical features such as location, depth of invasion, and margin status. Among them, PLR demonstrated the best predictive performance. This study provides valuable evidence for postoperative risk assessment and individualized follow-up management in early esophageal cancer patients.